1995
DOI: 10.1093/ajcp/103.6.685
|View full text |Cite
|
Sign up to set email alerts
|

Hamartoma of the Breast, an Underrecognized Breast Lesion:A Clinicopathologic and Radiographic Study of 25 Cases

Abstract: This study investigated the clinical, radiographic, and pathologic features of breast hamartoma. The patients ranged in age from 18 to 89 years, with a mean age of 45 years, and a median age of 43 years. Seventy-five percent of the patients were asymptomatic, other than reporting a breast lump. In two patients, the lesions recurred at 7 and 18 months after the initial resection. The clinical diagnoses were fibroadenoma in 10 cases, carcinoma in 5 cases, hamartoma in 4 cases, and phyllodes tumor and lipoma in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 0 publications
3
48
0
1
Order By: Relevance
“…This feature was noted in 55.5% of cases in the present study which was consistent with the rates reported in literature. [7,9,11] Cystic changes and apocrine metaplasia were noted in more than 50% of cases in our study. However this feature was observed to a lesser extent by few other authors.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…This feature was noted in 55.5% of cases in the present study which was consistent with the rates reported in literature. [7,9,11] Cystic changes and apocrine metaplasia were noted in more than 50% of cases in our study. However this feature was observed to a lesser extent by few other authors.…”
Section: Resultssupporting
confidence: 50%
“…In the present series 6 patients were above 35years of age. [1,5,8,9] 16 cases in the present study were suspected to be fibroadenomas and 2 cases were cystosarcoma phyllodes on clinical examination.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The presence of lobules and ducts differentiates hamartomas from fibroadenomas (11). However, hamartomas do not have specific diagnostic histological findings (4,5).…”
Section: Resultsmentioning
confidence: 99%
“…Pseudoangiomatous stroma and cystic changes may also be present in hamartomas [10]. Hamartomas represent between 0.1−0.7% all benign breast lesions.…”
Section: Discussionmentioning
confidence: 99%